The Role of Small & Medium Enterprises (SMEs) in Economic Development: The Algerian Experience - Mechaali, Bilal; Mahrez, Salah (جامعة عبدالحميد بن باديس مستغانم - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2020)
تهدف هذه الدراسة إلى التعرف على واقع المؤسسات الصغيرة والمتوسطة ومدى مساهمتها في تحقيق التنمية الاقتصادية في الجزائر، إذ يعتبر هذا القطاع المحرك الأساسي للتنمية الاقتصادية في العالم. أظهرت النتائج أنه رغم المجهودات التي بذلتها الجزائر لتطوير المؤسسات الصغيرة والمتوسطة إلا أن النتائج تبقى ضعيفة ومساهمة هذا النوع من المؤسسات في التنمية الاقتصادية لم ترقى إلى المطلوب. وهذا يتطلب تكثيف الجهود واتباع استراتيجية جديدة من شأنها رفع التحدي وتخطي الصعوبات التمويلية والتكنولوجية والتسويقية.. إلخ.
This study aims to identify the reality of SMEs and their contribution to the economic development in Algeria, as this sector is considered the main engine of economic development in the world. The results show that despite the efforts made by the Algerian state to develop SMEs, the results remain weak and the contribution of this type of enterprises to economic development (employment, export, GDP, value added) has not been met, Which requires intensifying efforts and a new strategy that will raise the challenge and overcome the difficulties of financing, technology and marketing ... etc.
Keywords: الدور -- المؤسسات الصغيرة والمتوسطة -- التنمية الاقتصادية -- الاقتصاد الجزائرى